A new species and record of Labiobaetis Novikova and Kluge, 1987 (Ephemeroptera: Baetidae) from India. Issue 4 (29th November 2022) - Sivaruban, T.; Srinivasan, Pandiarajan; Barathy, S.; Isack, Rajasekaran
Abstract: A new species of Labiobaetis Novikova and Kluge, 1987 is described based on the larval material from Tamil Nadu, southern India. The total number of Labiobaetis species in India is thereby increased to eight. Labiobaetis davamanii sp. n. is assigned to the L. sumigarensis group of species and it is compared with its other representatives as well as with other Labiobaetis species from the Indian subcontinent. Labiobaetis operosus Müller-Liebenau, 1984 from the L. operosus group is recorded for the first time from India. http://www.zoobank.org/urn:lsid:zoobank.org:pub:D0210970-8ECB-4486-8F02-50406135A215